An Efficient ICI Self-cancellation Scheme for High order Constellations - Habib, S. E. D.; Sayed, Reem I.; Hamed, Hisham M.; Fikri, Magdi (Technological Innovation in Engineering Research Vol. 1, 2022)
OFDM is an established modulation scheme in current broadband wireless mobile communication systems due to its high spectral efficiency and robustness to multipath interference. A well-known disadvantage of the OFDM system is its sensitivity to frequency offset caused by oscillator inaccuracies and the Doppler shift in the channel. The carrier frequency offset (CFO) causes loss of orthogonality, in which case the signals transmitted on each carrier are not independent of each other, thus leading to Inter Carrier Interference (ICI). Several techniques were developed to reduce the effect of frequency offset. These techniques can be grouped into two broad categories. The first category is termed the frequency offset estimation and correction category. The second group is termed the frequency-offset reduction category. In this second category, redundant modulation is necessary in order to achieve a trade-off between frequency offset sensitivity and bandwidth efficiency. In this chapter, a new scheme for ICI self-cancellation is proposed. The main idea of this scheme is first introduced using a simple single carrier system, and then it is applied to multicarrier modulation systems. In the proposed scheme each symbol is conjugated and repeated to build a data pattern in the transmitted stream. This data pattern will be utilized at the receiver to cancel the CFO errors. Thus, the transmitted stream takes the form X1X1*X2X2*X3X3* …. .At the receiver, each symbol suffers a CFO phase error. By calculating the phases of the received symbols R1A and R1B* corresponding to transmitted symbols X1 and X1*, averaging these two phases, the corrected received signal is calculated. Our proposed ICI self-cancellation scheme is, therefore, labeled as Conjugate Phase Additive (CPA) scheme. We apply the proposed single carrier modulation scheme to the OFDM system, and we propose two new conjugate techniques; Adjacent Conjugate Phase Additive OFDM (ACPA) and Symmetric Conjugate Phase Additive OFDM (SCPA). The proposed schemes are implemented and simulated in MATLAB environment. Their results are compared to the existing ICI self-cancellation schemes. In contrast to previous ICI cancellation schemes, these two schemes display a more graceful degradation of Bit Error Rate (BER) with the increase of the normalized frequency offset. Compared to the best published ICI self-cancellation scheme (ASR, SCSR), the SCPA scheme yields 7 dB improvement in BER over that of the SCSR at a normalized frequency offset = 0.1 for 256-QAM modulation type. The proposed 256-QAM ACPA OFDM ICI self-cancellation system is implemented using Xilinx System Generator tool for DSP design, co-simulated on Spartan3A DSP 3400 device FPGA, and compared with widely used CFO Error estimation and Correction technique (CFO-EC), using cyclic prefix, in terms of hardware resource usage and frequency offset analysis. The CFO correction hardware required for the ACPA scheme is less than 50% of that required for the classical CFO-EC scheme. Relative to the classical 128-QAM OFDM system with CFO-EC correction, the 256-QAM ACAP scheme achieves comparable immunity against frequency offset errors over the practical frequency offset range.